2017
DOI: 10.1038/s41598-017-04028-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Wheat660K SNP array-derived high-density genetic map for high-resolution mapping of a major QTL for kernel number

Abstract: In crop plants, a high-density genetic linkage map is essential for both genetic and genomic researches. The complexity and the large size of wheat genome have hampered the acquisition of a high-resolution genetic map. In this study, we report a high-density genetic map based on an individual mapping population using the Affymetrix Wheat660K single-nucleotide polymorphism (SNP) array as a probe in hexaploid wheat. The resultant genetic map consisted of 119 566 loci spanning 4424.4 cM, and 119 001 of those loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(134 citation statements)
references
References 73 publications
6
128
0
Order By: Relevance
“…The Wheat 660K SNP array was designed by the Chinese Academy of Agricultural Sciences and is based on hexaploid and tetraploid wheat, emmer wheat and Aegilops tauschii , and has the advantages of being genome‐specific, high‐density, efficient, cost‐effective and with a wide range of possible applications, and has also added numerous markers to the D genome (http://wheat.pw.usda.gov/ggpages/topics/Wheat660_SNP_array_developed_by_CAAS.pdf). The Wheat 660K SNP array has been widely used to identify genetic loci for quality traits, agronomic traits and disease resistance in common wheat (Cui et al , 2017; Jin et al , 2016; Yang et al , 2019).…”
Section: Development Of Marker‐assisted Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Wheat 660K SNP array was designed by the Chinese Academy of Agricultural Sciences and is based on hexaploid and tetraploid wheat, emmer wheat and Aegilops tauschii , and has the advantages of being genome‐specific, high‐density, efficient, cost‐effective and with a wide range of possible applications, and has also added numerous markers to the D genome (http://wheat.pw.usda.gov/ggpages/topics/Wheat660_SNP_array_developed_by_CAAS.pdf). The Wheat 660K SNP array has been widely used to identify genetic loci for quality traits, agronomic traits and disease resistance in common wheat (Cui et al , 2017; Jin et al , 2016; Yang et al , 2019).…”
Section: Development Of Marker‐assisted Selectionmentioning
confidence: 99%
“…Therefore, SNP arrays have been widely used by many breeders in a variety of academic research, including genome‐wide association (Guo et al , 2017; Kidane et al , 2019), linkage map construction and QTL mapping (Cui et al , 2017; Jin et al , 2016), population structure, and phylogenetic analysis (Kidane et al , 2019; Valluru et al , 2017). In the present study, we selected seven widely used high‐throughput wheat arrays (Wheat 9K, 15K, 35K, 55K, 90K, 820K and 660K arrays) and compared their performance in terms of SNP number, distribution, density and associated genes to assess their value and provide guidance for their better application in marker‐assisted breeding at the wheat genome level.…”
Section: Development Of Marker‐assisted Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a, b). This should be attributed to 4 1 7 4AL/5AL/7BS translocations during wheat's evolutionary history (Devos et al, 1995; 4 1 8 King et al, 1994). The translocation between 4A and 5A was observed in einkorn 4 1 9…”
Section: Homologous Regions In Barley and Wheat 4 0mentioning
confidence: 94%
“…According to the results of the distribution of polymorphism SNPs per 1 Mbp in each chromosome, we found that 2B, 4B, and 6A may have higher probability to be the chromosomes that contained PmTx45. 5B and 3B did not show a particularly high enrichment peak under this plot, because the chip had more on the loci of the two chromosomes (Cui et al 2017; Fig. 3C).…”
Section: Resultsmentioning
confidence: 94%